PENGARUH INTEGRATED MARKETING COMMUNICATION TERHADAP LOYALITAS PENGGUNA KARTU PASCA BAYAR HALO DI MALANG - Yuniaris, Wenny (Department of Management, 2011)
Fakultas Ekonomi Universitas Muhammadiyah MalangE-mail: kareynza@umm.ac.idABSTRACTThe aim of this research are to know the message of integrated marketing communication arecontent, structure, format, source, time, space, ettiquete, things, friendship, agreement, and symbol tobuild customer loyalty is trust, psychological commitment, word of mouth, that integrated marketingcommunication show with the effect to customer loyalty of Halo Post-Paid users at Malang. There isthree hypothesis, first is content, structure, format, source, time, space, ettiquete, things, friendship,agreement, and symbol are a message build in integrated marketing communication. Second, trust,psychological commitment, word of mouth to build customer loyalty. Third message of integratedmarketing communication affect to customer loyalty. The analysis is factor analys with rotated factorand multiple linear regression analys. The research result shown that message builder in integratedmarketing communication. Trust, psychological commitment, word of mouth are customer loyaltybuilder and than integrated marketing communication have significant influence to customer loyaltyof Halo Post-Paid users at Malang.Key word: message, integrated marketing communication, and customer loyalty